2021
DOI: 10.3390/cancers13081818
|View full text |Cite
|
Sign up to set email alerts
|

Radical Resection for Locally Advanced Pancreatic Cancers in the Era of New Neoadjuvant Therapy—Arterial Resection, Arterial Divestment and Total Pancreatectomy

Abstract: Aggressive arterial resection (AR) or total pancreatectomy (TP) in surgical treatment for locally advanced pancreatic cancer (LAPC) had long been discouraged because of their high mortality rate and unsatisfactory long-term outcomes. Recently, new chemotherapy regimens such as FOLFIRINOX or Gemcitabine and nab-paclitaxel have provided more adequate patient selection and local tumor suppression, justifying aggressive local resection. In this review, we investigate the recent reports focusing on arterial resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 104 publications
0
13
0
Order By: Relevance
“…Phase III randomized controlled trials revealed that extended lymphadenectomy with dissection of the nerve plexus did not prolong patient survival after resection 8–10 . In addition, effectiveness of SMA resection with pancreaticoduodenectomy in improving prognosis for head‐PDAC with SMA involvement has not been clarified 35 . Therefore, not only radical resection but also minimal postoperative complication leading to adjuvant chemotherapy are necessary to improve the prognosis of head‐PDAC with PL invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase III randomized controlled trials revealed that extended lymphadenectomy with dissection of the nerve plexus did not prolong patient survival after resection 8–10 . In addition, effectiveness of SMA resection with pancreaticoduodenectomy in improving prognosis for head‐PDAC with SMA involvement has not been clarified 35 . Therefore, not only radical resection but also minimal postoperative complication leading to adjuvant chemotherapy are necessary to improve the prognosis of head‐PDAC with PL invasion.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] In addition, effectiveness of SMA resection with pancreaticoduodenectomy in improving prognosis for head-PDAC with SMA involvement has not been clarified. 35 Therefore, not only radical resection but also minimal postoperative complication leading to adjuvant chemotherapy are necessary to improve the prognosis of head-PDAC with PL invasion. We also found a significant difference in DFS between the PL+ group and the PL− group; however, there was no significant difference in OS among these groups.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial invasion when talking about pancreatic head tumors mainly implicate the SMA or HA. Reconstruction can be performed as end-to-end anastomosis or through the use of conduits, such as interposition grafts (74). Particularly useful is the splenic artery that can serve both for interposition or transposition in several complex reconstruction strategies (75).…”
Section: Extended Pancreatoduodenectomy-arterial Managementmentioning
confidence: 99%
“…The majority of patients, however, are diagnosed at an advanced, unresectable stage with either systemic spread to distant organs or extensive local vascular tumor involvement 1. Advancements in systemic treatment and surgical techniques have increased the resection rate of the latter group, classified as locally advanced pancreatic cancer (LAPC) 8,10–12…”
mentioning
confidence: 99%